ANG II and Aldosterone Acting Centrally Participate in the Enhanced Sodium Intake in Water-Deprived Renovascular Hypertensive Rats - Lucera, Gabriela Maria; Menani, José Vanderlei; Colombari, Eduardo; Colombari, Débora Simões Almeida (Frontiers in Pharmacology, 2021)
Renovascular hypertension is a type of secondary hypertension caused by renal artery stenosis, leading to an increase in the renin-angiotensin-aldosterone system (RAAS). Two-kidney, 1-clip 2K1C rats have an increased sodium intake induced by water deprivation (WD), a common situation encountered in the nature. In addition, a high sodium diet in 2K1C rats induces glomerular lesion. Therefore, the purpose of this study was to determine whether ANG II and/or aldosterone participate in the greater sodium intake observed in 2K1C under WD. In addition, in 2K1C rats, we also aimed to verify the if central AT1 and mineralocorticoid receptor blockade would change the higher levels of arterial in water replete and WD 2K1C rats, since blood pressure changes can facilitate or inhibit water and sodium intake. Finally, possible areas activated during WD or WD followed by partial rehydration were also investigated in 2K1C rats. Male Holtzman rats (150-180 g) received a silver clip around the left renal artery to induce renovascular hypertension. Six weeks after renal surgery, a guide cannula was implanted in the lateral ventricle (LV), followed by 5 days of recovery before the protocols. Losartan (AT1 receptor antagonist) in the LV attenuated the water intake during the thirst test. Either icv losartan or RU28318 (mineralocorticoid receptor antagonist) reduced sodium intake and the combination of losartan and RU28318 totally blocked the salt intake induced by WD in 2K1C rats. The hypertension of 2K1C rats was not changed in hydrated or WD 2K1C by icv losartan and RU28318. There was Fos expression in the lamina terminalis and in the NTS in WD and a further increase in WD-PR. These results suggest the participation of central ANG II and aldosterone in the enhanced sodium intake in WD 2R1C rats. Central actions of ANG II and aldosterone are not important in the maintenance of hypertension in 2R1C rats with sodium available.